Efficacy and safety of first-line osimertinib treatment and postprogression patterns of care in patients with epidermal growth factor receptor activating mutation-positive advanced non-small cell lung cancer (Reiwa study): study protocol of a multicentre, real-world observational study. Issue 1 (4th January 2022) - Watanabe, Kageaki; Yoh, Kiyotaka; Hosomi, Yukio; Usui, Kazuhiro; Naka, Go; Kishi, Kazuma; Uemura, Kohei; Ohashi, Yasuo; Kunitoh, Hideo
Abstract : Introduction: Osimertinib, a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), is widely used as the first-line treatment for EGFR mutation-positive non-small cell lung cancer (NSCLC). Nevertheless, most cases ultimately acquire resistance to osimertinib, and no effective treatment has been currently established for cases having progressive disease (PD) with osimertinib. In clinical practice, EGFR-TKI therapy could be continued beyond response evaluation criteria in solid tumours (RECIST)-defined PD cases when they are clinically stable. Currently, the progression pattern of osimertinib and criteria for identifying patients who might benefit from osimertinib beyond PD are unknown. In addition, the efficacy and safety of osimertinib as the first-line treatment in real-world clinical practice remain unclear in Japan. This multicentre study was designed to evaluate the real-world data on first-line osimertinib and its post-treatment. Methods and analysis: The study enrols patients with EGFR mutation-positive, advanced or recurrent NSCLC who received EGFR-TKI as the first-line therapy after 1 September 2018, from October 2019 to August 2020, and those started on osimertinib will be followed up until August 2022. We will evaluate the efficacy and safety of the first-line osimertinib treatment, adherence to it, progression patterns on RECIST PD and subsequent treatment. Ethics and dissemination: All participating patients will provide written informed consent before entering the study. The protocol, amendments and patients' informed consent forms will be approved before study commencement by the institutional review board or independent ethics committee at each participation site (Lead Ethics Committee; Japan Red Cross Medical Center (26 April 2019, order number 976)). Patients will be anonymised before registration into the study and their anonymised data will be collected from the case report form. The results of this study will be presented at the national and international conferences and submitted for publication. Trial registration number: UMIN000038683.